2017
DOI: 10.1111/bjd.15087
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted role of hair follicle dermal cells in bioengineered skins

Abstract: Summary (Abstract)Background: The method to generate bioengineered skin constructs was pioneered several

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…Thus, it is known that e-CAF also induces migration in the human keratinocyte cell line (HaCaT) and primary dermal fibroblasts and human senescent dermal fibroblasts, although no effects on cell proliferation were found; additionally, it produced an improvement in the organization of cytoskeletal proteins F-actin and vimentin and was able to promote the production of ECM components, such as FN and Col I [25]. This study shows that e-CAF could also have beneficial effects on human mesenchymal stem cells from dermal papilla (HHDPCs), improving the capabilities of this cell population, which are of great importance on skin regeneration, because of their multipotential ability to generate different skin lineages [29,30,31,32,33,34,35,36]. In fact, our results showed that treatment with 1 µg/mL of e-CAF for 28 days promoted cell proliferation and 0.1 µg/mL of e-CAF concentrations increased cell migration ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is known that e-CAF also induces migration in the human keratinocyte cell line (HaCaT) and primary dermal fibroblasts and human senescent dermal fibroblasts, although no effects on cell proliferation were found; additionally, it produced an improvement in the organization of cytoskeletal proteins F-actin and vimentin and was able to promote the production of ECM components, such as FN and Col I [25]. This study shows that e-CAF could also have beneficial effects on human mesenchymal stem cells from dermal papilla (HHDPCs), improving the capabilities of this cell population, which are of great importance on skin regeneration, because of their multipotential ability to generate different skin lineages [29,30,31,32,33,34,35,36]. In fact, our results showed that treatment with 1 µg/mL of e-CAF for 28 days promoted cell proliferation and 0.1 µg/mL of e-CAF concentrations increased cell migration ability.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HHDPCs act as an important repository for tissue repair after injury generation, where rapid and dynamic changes in cell microenvironment induce processes of cell differentiation and phenotypic plasticity [32,33]. Moreover, several studies with animal models point out the interest in dermal papilla cells as an important cell subpopulation of the hair follicle in regenerative processes of the skin [34,35] and, additionally, HHDPCs have been postulated as a suitable source for the construction of bioengineered skin substitutes in cases where autografting is not the appropriate option due to its immunosuppressive properties, multipotentiality, and plasticity to differentiate into several mesenchymal lineages [36]. Thus, the ability to maintain or improve the capabilities of this cell population seems to be of great interest for skin regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The team of Hill and colleagues previously reported that hair follicle‐associated mesenchymal cells, specifically the hair‐inductive dermal papilla fibroblasts and dermal sheath fibroblasts, promote greater keratinocyte colony‐forming efficiency than dermal fibroblasts in 2D culture . In the current study, this group advances this knowledge further, demonstrating that dermal papilla and dermal sheath fibroblasts – normally associated with hair follicle regeneration – can also support interfollicular skin regeneration in organotypic cultures. Moreover, the full programme of epithelial proliferation and differentiation was observed as judged by the presence of a Ki67 + /K5 + basal layer and suprabasal expression of the keratinocyte differentiation markers K1 and loricrin.…”
mentioning
confidence: 54%
“…have reported improved α6 integrin expression in organotypic cultures containing dermal sheath vs. interfollicular skin‐derived dermal fibroblasts . Importantly, Higgins et al . provide conclusive evidence that hair follicle‐associated fibroblasts could be utilized in clinical applications to generate 3D skin reconstructs for transplantation without compromising skin integrity.…”
mentioning
confidence: 99%
See 1 more Smart Citation